2017
DOI: 10.1097/pts.0000000000000135
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Adverse Events Associated With Adult Moderate Procedural Sedation Outside the Operating Room

Abstract: Providers should take into account patient characteristics and procedure types when assessing the risks of harmful sedation-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Investigation into the safety of moderate IV sedation among obese women is limited. A retrospective review of 143,000 procedures performed with fentanyl and midazolam outside of the operating room at a tertiary care medical center found that BMI, age, co-morbidities, and type of procedure (gastroenterology and cardiology) were independently associated with adverse events [17]. This patient population was markedly older, with a mean age of 59.2 years, and had more co-morbidities than patients typically seen in freestanding abortion clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation into the safety of moderate IV sedation among obese women is limited. A retrospective review of 143,000 procedures performed with fentanyl and midazolam outside of the operating room at a tertiary care medical center found that BMI, age, co-morbidities, and type of procedure (gastroenterology and cardiology) were independently associated with adverse events [17]. This patient population was markedly older, with a mean age of 59.2 years, and had more co-morbidities than patients typically seen in freestanding abortion clinics.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Patients with greater ASA physical status and very young or very old patients appear to be at greater risk for cardiovascular and respiratory adverse events during PRS. 9 13 …”
mentioning
confidence: 99%
“…Events during PRS, such as respiratory depression, apnea, airway obstruction, or oxygen desaturation, have been reported in adult and pediatric patients and can result in significant morbidity. 8 , 9 , 13 15 Closed-claim analysis suggests that better monitoring during PRS could decrease the number of liability cases related to these events. 16 Pulse oximetry may not alert procedural teams to hypoventilation during PRS, particularly if supplemental oxygen is provided to the patient during procedures.…”
mentioning
confidence: 99%
“…A further positive element concerning robotic colonoscopy is represented by the data, recorded in normal clinical practice, related to the short learning curve necessary for the correct use of the medical devices; it is, however, necessary additional ad-hoc studies to con rm the signi cance of this gure. Despite conventional colonoscopy is currently the gold standard among the methods available for the screening of colorectal cancer [18], there are various risks factors associated to this type of procedure, ranging from cardiopulmonary complications [19,20], the perforation of the colon [21,22], to the risks associated with anaesthesia in painless conventional colonoscopy, especially if performed on paediatric patients or with comorbidities [23,24]. Besides, the fact that anaesthesia is not required in robotic colonoscopy, determines a series of social-organizational and also economic advantages related to the patient: greater autonomy of the subject being examined, lack of in uence of the procedure on the patient's driving ability, hence giving the possibility to the patient to come to examination unaccompanied, the ability to take important decisions or sign contracts within 24 hours of the procedure [25]; these are all elements that in uence the indirect costs related to the evaluation of technology, which have not been the subject of this study, but which nevertheless have an important role on the overall analysis of the study.…”
Section: Discussionmentioning
confidence: 99%